2019
DOI: 10.20849/jed.v3i1.564
|View full text |Cite
|
Sign up to set email alerts
|

Student Knowledge About the Water Cycle and Its Change in Different Interest Groups

Abstract: This study describes the role of interest in eighth-grade students’ (N=183) knowledge formation. Student knowledge was measured through open-ended questions at three time points: once before and twice after specific topics had been taught in a regular 45 min geography lesson. Student interest level was assessed using teacher ratings. Student answers to seven open-ended questions were coded and placed into one of three categories: everyday, synthetic, or scientific knowledge. Results showed that higher interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(86 reference statements)
0
6
0
1
Order By: Relevance
“…When children were asked to provide an answer to these problems, the answers included everyday experiences. Similarly, a recurrent finding was that objects stopped existing when children's visible connections with them were obstructed [12]. In all these examples, the concrete content of immediate senses and impressions was shown to be the basis for children's description of the process.…”
Section: Intuitive Conceptions and Modelsmentioning
confidence: 90%
See 1 more Smart Citation
“…When children were asked to provide an answer to these problems, the answers included everyday experiences. Similarly, a recurrent finding was that objects stopped existing when children's visible connections with them were obstructed [12]. In all these examples, the concrete content of immediate senses and impressions was shown to be the basis for children's description of the process.…”
Section: Intuitive Conceptions and Modelsmentioning
confidence: 90%
“…One example of a subject-specific learning progression was provided by Malleus and Kikas [12], who performed a teaching intervention concerning the water cycle and found in their analysis the three categories: everyday knowledge (a combination of visual and perceptual knowledge), synthetic knowledge (a combination of everyday knowledge with scientific knowledge), and scientific knowledge. Their results also showed that the change caused by the intervention was mainly an accumulation of new synthetic concepts.…”
Section: Previous Research On Children's Learning Progressionsmentioning
confidence: 99%
“…Exploring a socio-economical environmental problem through the inquiry phases exposes students to a situation where they have to make use of their everyday knowledge to form hypotheses and then through collecting, analyzing, and interpreting their collected data has a potential to direct students to use a more specific and scientific vocabulary and form synthetic or scientific understanding of the phenomenon. On the other hand, it must be noted here that there is a chance that students may acquire scientific-like descriptions by using scientific vocabulary about the phenomenon without real comprehension [63].…”
Section: From Everyday Knowledge To Scientific Understandingmentioning
confidence: 96%
“…Scientific knowledge means describing the phenomenon with accurate, abstract scientific vocabulary. According to Malleus and Kikas [63], synthetic knowledge can emerge as a consequence of (1) simplifying and/or integrating scientific information to match with daily experiences or (2) using scientific information bits without correct integration. Referring to Tytler [64], Malleus and Kikas [63] claim that for scientific understanding to form, there is a need for engaging students in learning designs, which emphasizes conceptual change.…”
Section: From Everyday Knowledge To Scientific Understandingmentioning
confidence: 99%
“…Siklus hidrologi adalah suatu fenomena lengkap yang terdiri dari beberapa sub proses yang tidak dapat langsung dilihat dengan mata, dan sulit dipahami (Malleus & Kikas, 2019). Materi siklus hidrologi bersifat abstrak dan menantang untuk dipahami oleh siswa sebab terdapat berbagai tahapan yang terjadi dalam siklus hidrologi yang tidak bisa dilihat secara langsung oleh indera manusia.…”
unclassified